Apatinib plus retinoic acid as maintenance for children with relapsed stage 4 high-risk neuroblastoma: Two case reports. Issue 26 (26th June 2020) - Jin, Mei; Zhang, Dawei; Zhao, Qian; Zhao, Wen; Huang, Cheng; Wang, Xisi; Duan, Chao; Su, Yan; Ma, Xiaoli
Abstract: Introduction: Metastatic neuroblastoma (NB) is an aggressive malignancy with a poor prognosis. Many patients present with relapsed high-risk NB after undergoing first-line treatment, and there is no standard therapy available in this setting. Patient concerns: The present study aimed to present the cases of 2 patients with recurrent high-risk NB. Diagnosis: Two children with International Neuroblastoma Stage System stage 4 high-risk NB chemotherapy. The disease recurrent after finishing the treatment. Interventions: Both patients (34 months old and 41 months old) experienced recurrence, received second-line treatment, and then received maintenance treatment using apatinib plus retinoic acid. The apatinib (10 mg/kg per day) and retinoic acid (160 mg/m 2 per day) were administered on alternating 2-week cycles, which was continued for 1 year. Outcomes: The 2 patients had achieved complete response by the 1-year follow-up after starting apatinib plus retinoic acid, and did not experience any adverse drug reactions. Conclusion: The outcomes from these cases suggest that apatinib plus isotretinoin might be an option for maintenance therapy in patients with recurrent high-risk NB.